Protracted case of vaginal prolapse and its remedial measures in a buffalo - SINGH, C P; PRASAD, SHIV; PRASAD, J K; SHAKTAWAT, J S (The Indian Journal of Animal Reproduction, 2023)
Protracted cases of cervico-vaginal/vaginal prolapse can be cured using vaginopexy under good hygienic conditions. However, supportive therapy in the management of the vaginal prolapse is mandatory. Parental administration of calcium preparation has been found to be beneficial in minimizing the tenesmus. The present technique coupled with parental calcium therapy could be adequate and effective tool for the management of recurrent/protracted cases of cervico-vaginal/vaginal prolapse in cattle and buffaloes.